Peningkatan Kesadaran Belajar dan Pendidikan Karakter Melalui Komunitas Belajar Anak - Rachmat Imam Muslim; Dian Kusumawati; Meilan Tri Wuryani; Ade Bagus Primadoni; Mar’atul Faida (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Technological advances bring positive and negative currents to the way students and the younger generation learn. Students can search for information and even the answers they need by utilizing technological advances. Unfortunately, the easy access to information received by students through technology without proper filtering or control will give rise to inequality in the younger generation, and negative foreign cultures sometimes affect our character as Indonesians. If bad habits are carried out continuously, they will stick and become bad character. Student character is a very important concern, and it is the homework of teachers and parents to complete it. Character will be the character, character, and behavior shown by the habits they carry out. Habits can grow through the environment in which they are formed, including family, school, and society. This community service has the aim of optimizing youth organizations as an environment for students to learn so that awareness grows in learning while at the same time embedding character values through the environment in which they are formed. Community service activities are carried out by forming study groups and utilizing existing facilities in the living environment, such as village halls, mosques, and parks. It is hoped that good habits in learning will stick with students and will increase awareness of learning.